BUDIDAYA IKAN AIR TAWAR SEBAGAI PENDORONG PENGEMBANGAN EKONOMI MASYARAKAT DI KANAGARIAN KOTO BARU KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Kasmuni, Cici; Suarto, Edi; Yuherman, Yuherman (Pendidikan Geografi, 2013)
This study aimed to obtain information, analyze and describe data on the cultivation of Freshwater Fish Resources For Drivers of Regional Economic Development in Koto Baru village Bayang district Pesisir Selatan region view of: 1) Capital cultivation of Freshwater Fish, 2) fish farming Income Level fresh water, 3) Marketing shape freshwater Fish Culture in Koto Baru village Bayang district Pesisir Selatan region.This research is a descriptive qualitative study using interview techniques. To answer this problem in the use of primary data and secondary data, primary data was collected through observation, interviews, discussions with informants and photographs taken in the field, while the secondary data got from the relevant parties.The results showed: 1) Capital freshwater fish farming on his own can of capital and there is also in the capital can be of assistance from others, the initial capital used in the cultivation of freshwater fish is around 30-50 million depending on the area of land which is managed, 2) the income level of freshwater fish farming in 1 year more than 96 million depending on the area of land that is managed, if the land is managed is not too large then the revenue was less than 96 million, 3) form of marketing of freshwater fish farming is on the market itself there are also traders who come to markets for freshwater fish culture